Análise de parâmetros operacionais da injeção contínua de vapor adaptado ao método sagd em reservatórios de petróleo pesado no nordeste brasileiro - Ferreira, Eduardo de Lima (2017)
The world scenario in the oil segment estimates a large oil reserve to be explored, about 1.7 trillion barrels, in 2015. In Brazil, more specifically, in the Northeast, there are large reserves of heavy oil, which needs specific techniques to be applied for such extraction. This operation beyond the technical peculiarity employed, there are also factors from the economic point of view that needs to be analyzed. Features which by conventional methods - immiscible gases and water injection - a promising recovery is practically unfeasible. In this aspect, the use of the thermal method - continuous steam injection adapted to the model of oil drainage by gravitational differential assisted by steam (SAGD) - is of paramount importance, since it allows a better sweeping efficiency, as it favors higher heat injections In the reservoir, and consequently, allowed better displacement of the oil. This method is widely used in the petroleum industry due to its efficiency, because when injecting steam on high temperature, this heat is transmitted to the oil, causing a significant decrease of its viscosity, and allowing better flow in the reservoir. The study was carried out using numerical simulation using the STAR (Steam, Thermal, and Advanced Processes Reservoir Simulator) program of the CGM (Computer Modelling Group) group - Version 2013. The operational and technical parameters used are: distance between wells, steam injection rate, completion interval, mesh configurations.